Symposium 7: The Literacies of Online Learning: A Linguistic-Ethnographic Approach to Research on Virtual Learning Communities - Goodfellow, Robin (Proceedings of the International Conference on Networked Learning, 2004)
This paper makes the case for a ‘social literacies’ approach to the analysis of interaction in virtual learning communities. It proposes a research agenda that will focus on questions of empowerment, marginalisation and exclusion, and the role of wider institutional and social practices in shaping the experience of participants in online learning environments. Some of the premises of the New Literacy studies are discussed, in the context of student writing and textual practices in online, global and multicultural learning environments. It is argued that there is a need for research into the way participants construct their own understanding of important social relations in these textual environments, and for the investigation of issues which contribute to the social shaping of education in the virtual domain. Such issues include: the maintenance of institutional and intellectual legitimacy through systems of assessment and the awarding of credit, the playing out of cultural difference amongst heterogeneous populations, and the nature of individual strategies of resistance to socialisation into virtual learning communities. Some research on online learning interactions is reviewed, and it is argued that key questions remain unexplored, about the nature of the communication practices developed by individuals and groups, and their role in constructing the experience of conflict for participants. A case is made for a linguistic-ethnographic approach to address the fact that social context in virtual communities is invisible and has to be inferred from linguistic evidence. An agenda of comparative studies is proposed, where the background of wider social literacy practice shared by participants in diverse online learning communities, is related to the different, more localised, practices of the communities themselves. Methods associated with this agenda are discussed, and a call is made for researchers interested in social literacies in virtual learning communities to collaborate on building a database of relevant evidence.